Pengaruh Literasi Keuangan dan Perilaku Keuangan Terhadap Minat Berinvestasi Mahasiswa Pendidikan Ekonomi UNS - Andriani, Hania; Kristiani; Sudarno (Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This study aims to identify (1) the effect of financial literacy on the interest in investment of students in the UNS Economics Education Study Program, (2) the effect of financial behavior on the interest in investment of students in the UNS Economics Education Study Program, (3) the effect of financial literacy and financial behavior on the interest in investment of students in the UNS Economics Education study program. This research is a quantitative research method with a population of 165 students in the UNS Economics Education Study Program batches of 2019 and 2020. The sampling technique used was proportionate random sampling with the data collection method using a questionnaires and the data analysis used was multiple linear regression analysis. The results of this study indicate that (1) there is a positive and significant influence of financial literacy on the interest in investment of students in the UNS Economic Education study program. (2) there is a positive and significant influence of financial behavior on the interest in investment of students in the UNS Economic Education study program. (3) there is a positive and significant influence of financial literacy and financial behavior on the interest in investment of students in the UNS Economic Education study program.